Migrant phenomena, cultural competence & health cares - Manuel Lillo Crespo; Isabel Casabona Martínez (Universidad de Alicante, 2012)
Nowadays, societies are exposed to multiple geographic movements so that bigger knowledge of cultural differences and equalities from distinct ethnic groups is needed and it becomes a profit for health organizations and programs, as well as recognizing the need of health professional education on adequate knowledge, skills and essential sources to provide sensitive culturally competent cares. That kind of culturally competent and congruent care could be defined as: "...the competence, that takes part in the caring process, which is within the nursing practice, that implies an anthropological view, from a qualitative perspective, with a holistic point of view, implying an specific nursing analysis...and so that is related with clinical practice, communication, professional and research ethics, nursing research, nursing education, management in cares, health education, etc..."; and would help to improve the caring proprocess of that type of culturally different patients, determining the good function of health systems, improving patient satisfaction and gradually arriving to changes in the practice of caring with patients from other cultural groups.